Numerical investigation of energetic effects of flow-through wall elements. (July 2017) - Hantsch, Andreas; Friebe, Christian; Döge, Sabine
Abstract: The energy efficiency of buildings is of interest for both science and industry. In order to reduce the energy demand for heating and cooling, a new flow-through wall element is proposed allowing to switch the effective properties of the wall. By means of numerical modelling and simulation, the energetic effects of the wall element are studied for different cities (i.e. climatic conditions), flow speeds through the wall element, and volumetric heat capacities of the wall. Simulations at sufficiently small time steps for an entire year allow to determine the maximum heating and cooling loads, and the respective annual energies by integration. This reveals that the flow-through wall element is beneficial for most of the conditions and cities. For instance, it can be observed that the annual heating energy can be reduced to approximately half of those of a simple wall almost irrespective of the city. Contrary, the annual cooling energy reduction strongly depends upon the city and the flow speed. The primary energy analysis revealed a distinct minimum which is assigned to flow speeds of approximately 1 m s − 1 . Abstract : Highlights: Flow-through wall element is beneficial for most of the conditions and cities. Annual heating energy can be halved. Annual cooling energy has a minimum at particular flow speed. Primary energy demand has a minimum at a flow speed of approx. 1 m/s.